Night-Flight Readiness Analysis of Djalaluddin Airport Using Open-Source Satellite Imagery and Public Documents - Sri Susanty Dukalang (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2026)
Night-flight readiness at regional airports in developing countries are often overlooked, despite their crucial role in connecting communities and supporting emergency services. This study evaluates the readiness of Djalaluddin Airport in Gorontalo, Indonesia, for night flights by combining open-source satellite imagery with publicly available aviation records. Using Sentinel-2 and VIIRS nighttime imagery from 2020 to 2023, we examined runway lighting patterns, surrounding infrastructure, and overall nighttime illumination. These data were cross-checked against NOTAMs, airport master plans, and official flight schedules from the Indonesian Directorate General of Civil Aviation. The analysis revealed that only 68% of runway edge lights are reliably visible in satellite imagery, while 42% of approach paths lack sufficient illumination. These deficiencies are consistent with reported delays during night operations and the absence of formal night-landing procedures. Unlike previous studies that focus primarily on major international airports, this research applies a low-cost, satellite-based assessment to a regional airport in Southeast Asia, demonstrating its applicability in resource-limited settings. The methodology offers a practical, replicable approach that does not require expensive on-site surveys. By integrating remote sensing into routine safety audits, airport authorities can make evidence-based decisions about lighting improvements, prioritizing investments where they are most needed. Ultimately, this study presents a scalable, data-driven framework that can strengthen night-flight safety and operational reliability in under-resourced aviation systems worldwide.